2020
DOI: 10.1177/0260106020919629
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of street food to dietary intake of habitual urban consumers: A cross-sectional study in Kampala city, Uganda

Abstract: Background: Street food has continued to be a popular food source in the urban settings of developing countries and is proving to be a vital urban dietary source. However, its dietary contribution among urban populations is yet to be comprehensively understood. Aim: To assess how street food contributes to the dietary intake of habitual street food consumers. Methods: We conducted a community-based cross-sectional study among habitual street food consumers in Kampala city. We defined habitual intake as consump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 15 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…The dietary and nutrient compositions of meals eaten away from home could explain the positive associations between EAFH and overweight and obesity. EAFH is associated with the consumption of foods that are high in energy, fat, sugar, and salt, but low in fruits, vegetables, and micronutrients [ 5 8 26 ]. Orfanous and colleagues reported that EAFH was associated with excessive energy intake and lower physical activity, which are both risk factors of weight gain [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The dietary and nutrient compositions of meals eaten away from home could explain the positive associations between EAFH and overweight and obesity. EAFH is associated with the consumption of foods that are high in energy, fat, sugar, and salt, but low in fruits, vegetables, and micronutrients [ 5 8 26 ]. Orfanous and colleagues reported that EAFH was associated with excessive energy intake and lower physical activity, which are both risk factors of weight gain [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Culturally, this can be explained by the fact that women are responsible for food preparation in Uganda. Previous studies have reported that in urban areas of Uganda, more men eat at street food establishments than women [ 8 ], which suggests that men are more susceptible than women to the dietary deficiencies and/or excesses of away-from-home foods. In one recent Ugandan study, men consumed more energy and fat from street foods than women [ 8 ], which concurs with the findings of a Kenyan study [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations